2020
DOI: 10.1002/ehf2.13143
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial function and maximal exercise capacity in heart failure with preserved and mid‐range ejection fraction

Abstract: Aims Exercise intolerance is the leading manifestation of heart failure with preserved or mid-range ejection fraction (HFpEF or HFmrEF), and left atrial (LA) function might contribute to modulating left ventricular filling and pulmonary venous pressures. We aim to assess the association between LA function and maximal exercise capacity in patients with HFpEF or HFmrEF. Methods and results Sixty-five patients, prospectively enrolled in the German HFpEF Registry, were analysed. Inclusion criteria were New York H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 54 publications
2
15
0
2
Order By: Relevance
“…All patients were stable and fully recompensated before inclusion into this study. One hundred thirty-one consecutive patients with a diagnosis of HF with preserved ejection fraction (HFpEF) or mid-range ejection fraction (HFmrEF) were evaluated at the Charité University Hospital, Berlin, Germany, and prospectively enrolled in the German HFpEF Registry (data previously published 7 ); 116 consecutive patients with HF evaluated at the Cardiac Rehabilitation Centre, Veruno, Italy, in the same time frame were retrospectively enrolled.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All patients were stable and fully recompensated before inclusion into this study. One hundred thirty-one consecutive patients with a diagnosis of HF with preserved ejection fraction (HFpEF) or mid-range ejection fraction (HFmrEF) were evaluated at the Charité University Hospital, Berlin, Germany, and prospectively enrolled in the German HFpEF Registry (data previously published 7 ); 116 consecutive patients with HF evaluated at the Cardiac Rehabilitation Centre, Veruno, Italy, in the same time frame were retrospectively enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria of the German HFpEF Registry have been previously published. 7 Inclusion criteria for patients included at the Veruno Centre were (i) known LV systolic dysfunction (LVEF ≤ 50%); (ii) age ≥ 18 years; and (iii) New York Heart Association (NYHA) functional class ≥ II. For both populations, patients were ineligible in the presence of acute coronary syndrome or cardiac surgery/percutaneous intervention during the past 3 months, haemodynamic relevant pericardial disease, significant mitral annular calcification, congenital heart disease, previous cardiac transplantation, restrictive cardiomyopathy, severe chronic obstructive pulmonary disease, severe kidney disease, or severe liver disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…108 However, exercise intolerance is also a classical feature of HFpEF and has been shown to be closely associated with LA function in HFpEF patients without AF. 109,110 Furthermore, in a large cohort of patients with AF, cardiopulmonary exercise testing showed that diastolic function rather than cardiac rhythm predicted maximal VO 2 . 111 These studies suggest that LA myopathy and HFpEF play critical roles in the development of exercise intolerance in patients with AF.…”
Section: Exercise Intolerancementioning
confidence: 99%
“…There is increasing evidence that LA dysfunction contributes to cardiorespiratory symptoms and exercise capacity [22,23]. A strong association between reduced LALSr and impaired exercise capacity was observed in patients with HF with preserved or mid-range ejection fraction [24]. Impaired LALSr and LALSct have also been linked to abnormal exercise dynamics and elevated pulmonary pressure in these patients [11,25].…”
Section: Mechanism For La Function and Exercise Capacitymentioning
confidence: 99%